Genotype distribution of methylenetetrahydrofolate reductase A1298C and C677T gene in Indonesian infertile men (Medical Journal of Indonesia, 2012)
Background: Methylenetetrahydrofolate reductase (MTHFR) is an important enzyme of folate and methionin metabolism, making it crucial for DNA synthesis and methylation. Variants of MTHFR C677T and A1298C gene result in reduced plasma folate levels and increase the susceptibility to spermatogenic arrest. This research aims to analyses MTHFR C677T and A1298C gene polymorphism in Indonesian infertile men with azoospermia and oligozoospermia.Methods: This cross sectional study takes 3 mL of blood from 150 infertile men with oligozoospermia and azoospermia. MTHFR gene is analyzed using polymerase chain reaction technique (PCR) with specific primers. PCR-RFLP analysis of the MTHFR gene using restriction enzymes MboII and HinfI determines allotypes, both of SNP A1298C and C677T in oligozoospermia and azoospermia in Indonesian population.Results: The results show that the distribution of allotypes of MTHFR gene SNP A1298C and A677T is not significantly different (p>0.05) between patient groups with oligozoospermia and azoospermia.Conclusion: MTHFR gene polymorphisms, both of SNP A1298C and C677T are not associated with male infertility in Indonesian men including patients with severe oligozoospermia and azoospermia. (Med J Indones 2012;21:23-7)Keywords: DNA methylation, MTHFR, spermatogenic arrest